Dynamics of microbial biomass and respiratory activity during late summer in a site of Arctic Kongsfjorden - Maurizio, Azzaro; Rosabruna, La Ferla; Giovanna, Maimone; Filippo, Azzaro; Franco, Decembrini; Carmela, Caroppo; Leonardo, Langone; Federico, Giglio; Stefano, Miserocchi; Stefano, Aliani (Frontiers in Marine Science, 2014)
Prokaryotic and phytoplankton interaction plays a key role in relevant processes such as carbon fluxes and nutrient regeneration (Zaccone et al., 2004). Sinking biogenic particles drive respiration in the ocean and related studies are important to determine the flow of organic matter along the water column (Martin et al., 1987; Karl et al., 1987). However, organic matter collected by sediment traps (Langone et al., 2000) or the studies of the disequilibrium 234Th/238U (Aliani et al., 2004) does not take into account the entire pool of oxidable organic matter, which includes the dissolved organic matter present in the seawater. The study of microbial respiration rates instead fills this gap, since respiration includes oxidation of both dissolved and particulate organic mater, providing an integrated estimate of the carbon utilization in the sea (Azzaro et al., 2006). In this context, a study on an Arctic fjord (Kongsfyorden, Svalbard) was done in late summer 2013, with the purpose of knowing the variability of prokaryotic and phytoplanktonic biomass and of microbial remineralization rates over short time scales in a coastal station (water depth ~105 m), where a mooring (Mooring Dirigibile Italia, MDI: 78° 54 .859'N; 12° 15. 411' E) is positioned. The Kongsfjorden was affected by inflow of Atlantic water as well as glacier melt water runoff (Cottier et al., 2005). The experiment comprised 5 samplings performed during a 7 day period in MDI station. For each sampling, photosynthetically active radiation (PAR), temperature and conductivity (salinity) were recorded along the water column with a PNF-300 profiler and a SeaBird Electronics SBE-911 plus profiler, respectively . Water samples were taken at five different depths (surface, 5, 25, 50 and 100 m) to determine nutrients, particulate organic carbon, prokaryotes and phytoplankton biomass, and community respiration. In addition, prokaryotes sunk with the particulate matter were studied into the sediment trap positioned in the MDI during the period between June and September 2013. The latter assessment allowed us to determine the flow of prokaryotes, conveyed from organic matter sinking, throughout the summer. Due to melting of the glaciers in the surface water of the study site, there were sediment loads which strongly limited light penetration and low irradiance (~0.7% E0+) at 5 meters below the surface. Along the water column the intrusion of the salty and warm Atlantic water was visible in the study site and the warm core was at about 25 m depth. PO4 concentrations ranged between 0.43 (surface) and 1 µM (100 m) and in general the values increased from surface to bottom. NH4, NO2 and NO3 significantly changed along the vertical and with time and varied between 0.39 and 5.05µM, 0.01 and 0.67µM, 0.001 and 4.18µM, respectively. Prokaryotic abundances and cell volumes ranged between 5.6 and 15.9 E+05 cells ml-1 and 0.033 and 0.093 µm3, respectively. These latter parameters showed a peak at 25 m depth in the core of incoming Atlantic water. This evidence was not determined in chlorophyll a (range 0.034-1.102 mg m-3), where the highest values were determined at the surface and 5 m depth. Speculations will be made on the variability of the fluxes of carbon remineralization in the short time scale and the different role played by autotrophic and heterotrophic communities along the water column.